Jumpstart UIKit : Learn to Build Enterprise-Level, Feature-Rich Websites that Work Elegantly with Minimum Fuss - Shenoy, Aravind (Apress, 2020)
Learn to build modern, sleek, and powerful websites quickly and easily with UIKit, an open-source, responsive, and lightweight framework. This book reveals the massive potential of this amazing framework to help you prototype, develop, and customize your web projects as per your business requirements Responsive web design is imperative nowadays as mobile sites become the de-facto standard. UIKit makes front-end design easier and helps speed up the development process significantly. You can build enterprise-level, feature-rich websites that work elegantly with a wide range of different device sizes and resolutions with minimum fuss. You'll play with the mobile-first grid component and an expansive set of intuitive CSS elements. UIKit simplifies the difficult task of crafting intricate and robust websites. Instead of loads of theory, this good read will help you get comfortable with the various utilities using comprehensive coding examples in an easy-to-understand manner. You will: Set up the UIKit's required build tools to get started Create a fully responsive, fluid, and nested grid layout Use UIKit to take your first steps in responsive web design Play with the wide-range of CSS components and elements Work with design web elements such as Navigation, Cards, Modals, Forms, and Accordion.